2018
DOI: 10.1016/j.autrev.2017.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the detection of citrullination and carbamylation

Abstract: Carbamylation and citrullination are both post-translational modifications against which (auto)antibodies can be detected in sera of rheumatoid arthritis (RA) patients. Carbamylation is the chemical modification of a lysine into a homocitrulline, whereas citrullination is an enzymatic conversion of an arginine into a citrulline. It is difficult to distinguish between the two resulting amino acids due to similarities in structure. However, differentiation between citrulline and homocitrulline is important to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 32 publications
0
47
0
Order By: Relevance
“…However, a difficulty is associated with distinguishing citrullinated proteins from carbamylated proteins: not only the cross-reaction of antibodies in patient serum, but also that of commercially available antibodies for experiments. Although the antimodified citrulline (AMC)-Senshu antibody [56] and antibody against the deca-citrulline peptide (F95) [57] have been used in many studies on citrullinated antigens, both were shown to bind to carbamylated antigens [9,58,59]. These findings indicate the potential misinterpretation of carbamylated antigens as citrullinated antigens in many previous studies because citrullinated proteins and carbamylated proteins may both be produced by activated neutrophils, including NETs-forming neutrophils, as discussed above.…”
Section: Technical Issues For Discriminating Citrullinated Antigens Fmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a difficulty is associated with distinguishing citrullinated proteins from carbamylated proteins: not only the cross-reaction of antibodies in patient serum, but also that of commercially available antibodies for experiments. Although the antimodified citrulline (AMC)-Senshu antibody [56] and antibody against the deca-citrulline peptide (F95) [57] have been used in many studies on citrullinated antigens, both were shown to bind to carbamylated antigens [9,58,59]. These findings indicate the potential misinterpretation of carbamylated antigens as citrullinated antigens in many previous studies because citrullinated proteins and carbamylated proteins may both be produced by activated neutrophils, including NETs-forming neutrophils, as discussed above.…”
Section: Technical Issues For Discriminating Citrullinated Antigens Fmentioning
confidence: 99%
“…While several other methods for detecting citrullination have been reported [60], the most reliable is mass spectrometry (MS); however, this involves a detailed procedure to identify citrullinated proteins from many other proteins (reviewed by Verheul et al [59]). High-performance liquid chromatography (HPLC) is also useful for focusing on one specific protein and discriminating citrullination from carbamylation [61].…”
Section: Technical Issues For Discriminating Citrullinated Antigens Fmentioning
confidence: 99%
“…This cross‐reactivity is also detected in patients in which anti‐CarP and ACPA responses show cross‐reactivity to varying degrees . Furthermore, preliminary data illustrated that an ACPA/AAPA monoclonal antibody can be cross‐reactive, and commercially available (polyclonal) antibodies are often unable to distinguish between different citrullinated and carbamylated residues . Together, these observations hint toward a cross‐reactive antibody response targeting citrullinated, carbamylated, and acetylated proteins.…”
Section: Hypotheses Elucidating Mechanisms Of Autoimmunity In Ramentioning
confidence: 99%
“…This exact mass increment also occurs on one of the most frequent modifications, the deamidation of asparagine (Asn) or glutamine (Gln), which is a spontaneous non‐enzymatic conversion of an uncharged side‐chain residue (Figure ). Occurrence of deamidated and citrullinated residues in the same peptide leads to interference during precursor ion isolation and can result in incorrect assignments of modified amino acids (ie, co‐isolation of other species), which leads to mixed or contaminated MS/MS spectra . In fact, deamidation of Asn/Gln occurs much more frequently than citrullination.…”
Section: Mass Spectrometry Applied To the Study Of Citrullination In mentioning
confidence: 99%
“…Occurrence of deamidated and citrullinated residues in the same peptide leads to interference during precursor ion isolation and can result in incorrect assignments of modified amino acids (ie, coisolation of other species), which leads to mixed or contaminated MS/ MS spectra. 35 In fact, deamidation of Asn/Gln occurs much more frequently than citrullination. Thus, this is the major problem leading to a high degree of ambiguity during data interpretation.…”
Section: Mass Increment Of 09840 Da Is Not Citrullination Specificmentioning
confidence: 99%